Perbedaan Pengaruh Karakteristik Perusahaan, Karakteristik Industri Dan Makro Ekonomi Terhadap Return Saham Antara Bank Syariah Dan Non Syariah Di Indonesia - Ratnasari, Anggi Febria; , Dra. Wafiatun Mukharomah, M.M (2015)
This study aims to determine the differences between Islamic banks with a firm non-Islamic banks. The samples are 19 companies listed in the Indonesia Stock Exchange in 2011-2013. The technique of taking the sample with purposive sampling method. Data analysis method used descriptive analysis, normality test, homogeneity test, and test different. Results from this study can be concluded that the characteristics of the company measured by profitability (p-value = 0.041) and leverage (p-value = 0.009) between Islamic banks and non sharia there is a difference, because the test results is less than p-α (<0, 05). The Industry characteristics as measured by type of industry ((p-value = 0.001) and the size of the bank (p-value = 0.000), between banks and non-Islamic sharia there is a difference, because the test results is less than p-α (<0.05). While Macroeconomic measured by inflation (p-value = 0.001), the dollar exchange rate (p-value = 0.000) and interest rates, among Islamic banks and non sharia there is a difference, because the test results is less than p-α (<0.05).